2017
DOI: 10.1051/epjconf/201714302126
|View full text |Cite
|
Sign up to set email alerts
|

Determination of flow-rate characteristics and parameters of piezo pilot valves

Abstract: Abstract. Pneumatic directional valves are used in most industrial pneumatic systems. Most of them are two-stage valves controlled by a pilot valve. Pilot valves are often chosen randomly. Experimental studies in order to determine the flow-rate characteristics and parameters of pilot valves were not conducted. The paper presents experimental research of two piezo pilot valves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Drilling is a crucial machining process used in many industrial applications involving hole cutting, which range from those in the tooling sector to those in the machine and space industries [ 1 , 2 ]. A study of the machining operations performed in 145 companies revealed that drilling is the most common machining process in manufacturing [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drilling is a crucial machining process used in many industrial applications involving hole cutting, which range from those in the tooling sector to those in the machine and space industries [ 1 , 2 ]. A study of the machining operations performed in 145 companies revealed that drilling is the most common machining process in manufacturing [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of deep hole cutting, accuracy is essential, as it greatly affects the operation of machines. If holes are drilled incorrectly, for example, in pneumatic control valves, the fluid flow (flow characteristics) may be affected [ 2 ]. The hole quality is generally assessed using the following geometrical and dimensional errors: cylindricity, straightness, roundness and diameter [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in the figure, the critical pressure ratio was 0.44 at a supply pressure of 500 kPa. The critical pressure ratios of commercially available valves are approximately 0.3 to 0.45 [17,19]. The path is geometrically symmetrical because the flow path is between the orifice and the ball.…”
Section: Static Characteristicsmentioning
confidence: 99%
“…In case of noncontacting gas face seals, one of the methods that allows for keeping stable layer of medium, is introduction of different geometrical modifications (microstructures) on the working rings races. This can be radial or spiral grooves [1,2] or textured face surface [3,4] and the others parameters [5,6]. Change of the faces of sealing rings entails changes of the fluid film dynamic properties and temperature [7][8][9].…”
Section: Introductionmentioning
confidence: 99%